Üzletasszonyok és üzletemberek: női és férfi vállalkozók az 1990-es évek elején (Szociológiai Szemle, 2024)
The number of enterprises are increasing all over Europe. This increase is due to women’s growing inclination to launch on an enterprise. Although this is an important factor, it has been fairly disregarded up till now in our region. Much attention has been paid to the appearance of female enterpreneurs in the last decades in market economies. It is not so much the case in Hungary.After displaying the new patterns of the female employment in Western-Europe the paper compares the similarities and differences between Hungarian female enterpreneurs and on the one hand Western-Europe female entrepreneurs, and on the other Hungarian male entrepreneurs and their enterprises.The analysis is based on a random sample of Hungarian small entrepreneurs. The survey was carried out in the late 1993. The main questions are focused on the following subjects: relationship between entrepreneurship and unemployment, motivations of women and man to set up and enterprise, the relation of schooling and entrepreneurial motives, the combination of family and work, the segregation of male and female entrepeneurial fields, discrepancy in earnings of female and male entrepreneurs.